HIV/AIDS Epidemic Among Older Adults in China During 2005–2012: Results From Trend and Spatial Analysis. (3rd April 2014) - Xing, Jiannan; Li, Yin-ge; Tang, Weiming; Guo, Wei; Ding, Zhengwei; Ding, Guowei; Wang, Liyan; Qin, Qianqian; Xu, Yan; Qian, Shasha; Mahapatra, Tanmay; Wang, Lu
Abstract : This study described the spatial distribution and trend of HIV/AIDS among older adults in China, and we tried to identify the clustering of infections and translocation of hotspots during the study period. Abstract : Background.  Recent studies have indicated an increasing burden of human immunodeficiency virus (HIV)/AIDS among older adults. Methods.  All identified people living with HIV/AIDS (PLWHA) recorded through the Chinese HIV/AIDS CRS during 2005–2012 were included in the study, except for the cases that lacked specific spatial information. Trend tests and spatial analyses were conducted. Results.  Information about 73, 521 PLWHA (aged ≥50 years) was collected during 2005–2012. Three provinces—Guangxi, Henan, and Yunnan—accounted for 54.4% of the identified cases during the study period. Compared with 2005, the ratio between residents and migrants among the study population decreased to 40.1% in 2012. The ratio of HIV-infected patients to AIDS patients and the ratio of males to females increased gradually among older infected adults. Results of spatial analysis indicate a clustered distribution of HIV/AIDS among older adults throughout the country. Hot spots were observed in 4 provinces (Guangxi, Henan, Yunnan, and Sichuan) and 1 municipality (Chongqing). A trend from central provinces toward southern provinces was also identified. Conclusions.  The number and proportion of HIV/AIDS among older adults have increased in recent years. The hot spots showed movement from central to southern China. A focused intervention strategy targeting the older PLWHA is urgently required in China.